Konsep Dasar Pendidikan Pesantren dalam Sudut Pandang Rahmah El Yunusiyyah - Ahmada, Futiha Alambarra Amaan; Anshory, Muhammad Isa (TSAQOFAH, 2024)
Pesantren is an educational institution in the form of a dormitory that plays a dual role in teaching general insights and providing guidance and care to students for 24 hours / day. The basic concept of education in pesantren includes Islamic religious learning, boarding guidance, and instilling values and norms. The pesantren equips its students with specific religious insights and general knowledge accompanied by religious spiritual guidance, character education, and the cultivation of noble manners. One of the educational reformers who carried the concept of pesantren in her educational thought was Rahmah El Yunusiyyah. To find out how Rahmah El Yunusiyyah's basic concept of education towards pesantren, this research intends to explain Rahmah El Yunusiyyah's educational thinking used in building her school. In conducting this research process, the author uses a literature study-based qualitative method in which the final findings of the research are in the form of descriptive explanations. From the analysis, it is known that in the establishment of her school, Rahmah El Yunusiyyah specialized in education for women. Meanwhile, the basic concept of pesantren education promoted by Rahmah El Yunusiyyah is summarized in the triangle of woman's education which includes education in schools, education in dormitories, and education in the community. This concept applies the cooperation of educators/teachers, caregivers in dormitories, parents and the community in providing education to children. This aims to produce a generation of women who are competent in their role as mothers who are the first school for their children in the future.